A steep price [compact disc, unabridged] - Dugoni, Robert (Dugoni, Robert. Tracy Crosswhite series., 2018)
When a missing woman turns up dead at the bottom of a well, Tracy must find out who killed her and if it had to do with an arranged marriage, while also hiding the secret of her own pregnancy.